2015
DOI: 10.1016/j.dib.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Survey of socio-economic and contextual factors of households׳ energy consumption

Abstract: We present a set of data relating to the investigation of the Tunisian Company of Electricity and Gas (STEG). The census is done on a sample of 3000 electrified households. The questionnaire is divided into three main sections: household socioeconomic status, contextual characteristics related to their housing and technical characteristics of equipments used. The objective of this survey is to achieve a reliable and detailed knowledge on the behavior of household energy consumption, particularly for energy sav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The sample survey is based on a subset of women in the construction industry in Lagos State. Similar researches that used field survey to obtain their data can also be found in [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . A survey research design was conducted on the identified sample.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 80%
“…The sample survey is based on a subset of women in the construction industry in Lagos State. Similar researches that used field survey to obtain their data can also be found in [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . A survey research design was conducted on the identified sample.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 80%
“…Details on other research aimed at studying the nature, causes, distribution and management of externalizing behavior in children and adolescents can be found in [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . Sample (field) survey was used to obtain the data, similar researches that used field survey to obtain their data can also be found in [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…It should be noted that mortgage valuation is key to determination of professional fee. Surveys are very vital in understanding and predicting key population characteristics [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . In this case, Ikeja, Lagos, Nigeria was chosen for the research and the study area is indicated in Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%